2016
DOI: 10.1016/j.jtcvs.2016.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch reconstruction using a Kommerell diverticulum for hypoplastic left heart syndrome with a right aortic arch

Abstract: We describe right aortic arch reconstruction using a Kommerell diverticulum in a Norwood modification for hypoplastic left heart syndrome (HLHS) with a hypoplastic right aortic arch, a Kommerell diverticulum, and a right-sided descending aorta. This method removes the retroesophageal component of the aorta and ensures an unobstructed aortic pathway and a sufficient aortopulmonary space with the advantage of growth potential. DISCUSSION Right aortic arch hypoplasia in a variant of HLHS is extremely rare. Few re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Interestingly, review of literature on HLHS with RAA revealed common association with unusual origin of either the innominate or left subclavian artery. 2 , 3 , 4 , 5 In our case, it arose from the distal pulmonary artery. To potentially avoid any steal of pulmonary blood flow, we chose to ligate it.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Interestingly, review of literature on HLHS with RAA revealed common association with unusual origin of either the innominate or left subclavian artery. 2 , 3 , 4 , 5 In our case, it arose from the distal pulmonary artery. To potentially avoid any steal of pulmonary blood flow, we chose to ligate it.…”
Section: Discussionmentioning
confidence: 53%
“…Only one successful case of Norwood modification for RAA with right descending thoracic aorta has been described using a large diameter Kommerell diverticulum. 5 In this case, following excision of the ductus, the large Kommerell diverticulum was mobilized to the right side of the trachea and anastomosed to the neoaortic root. 5 However, the technique can only be used when there is an unusually large diverticulum.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The repair was performed by transecting the duct and resecting the ductal tissue, bringing the Kommerell diverticulum in front of the trachea, and performing a double-barrel type of Damus/Kaye/Stansel anastomosis, anastomosing, to the roof of this neoaorta, the distally transected AAo. 7 Our case presented with the hypoplastic AAo, hypoplastic RAA, coarctation, and right descending Ao. In this variant, the location of the PA, to the left of the AAo but with the aortic arch running toward the opposite side, precludes the repair most commonly performed in patients with left aortic arch (and in at least 2 of those with an RAA and circumflex, retroesophageal aorta, described in previous reports), that includes the more typical amalgamation of the proximal portion of the transected PA with the AAo, as originally described by Norwood.…”
Section: Commentmentioning
confidence: 78%